Abuse of Circumstances as a Ground for Contract Cancellation: A Juridical Review of Lease Agreement Case No. 171/Pdt.G/2022/PN.Plk - Gunawan, Rizka Putri; Lia Amaliya (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2025)
The Indonesian Civil Code (KUH Perdata) does not explicitly regulate the doctrine of misuse of circumstances (misbruik van omstandigheden). However, in legal practice, this concept increasingly serves as a basis to cancel agreements, especially when one party exploits the urgency, dependence, or weakness of another party often resulting in injustice. This doctrinal development is particularly relevant in cases involving lease agreements, where contractual imbalances are common. This research uses normative legal analysis and case study approaches, focusing on Decision No. 171/Pdt.G/2022/PN.Plk. Through document review and legal reasoning, it is shown how the judges considered the existence of an unfair advantage the lease agreement contained terms that significantly disadvantaged the tenant. The court found clear evidence of imbalance arising from the stronger bargaining position of the landlord relative to the tenant's vulnerable situation. Based on this, the judges accepted the misuse of circumstances as a valid reason to cancel the agreement and restore justice for the disadvantaged party. The findings highlight the crucial responsibility of judges to actively uphold justice and protect vulnerable parties in contractual relations, especially lease agreements. Moreover, the research suggests an urgent need for clearer and stricter regulation of the doctrine of abuse of circumstances in Indonesian contract law. Ensuring more robust legal provisions would enhance legal certainty and guarantee fairness for all parties involved in contractual agreements.